A Study to Assess the Effectiveness of Planned Teaching Programme on Knowledge Regarding Family Planning Methods among Eligible Couple in Selected Urban Area of Gwalior City (M.P.) - Masih, Pratik; Banappagoudar, Sudharani; Pancholi, Ambali; Anil, Mini; Sikarwar, Nirdesh (International Journal of Membrane Science and Technology, 2023)
Family planning is critical for limiting population increase and promoting family well-being. However, there is a dearth of awareness and information about various family planning options among eligible couples in many urban areas. The purpose of this study is to determine the efficacy of a planned training programme on understanding of family planning methods among eligible couples in a designated urban region of Gwalior City, Madhya Pradesh. Purpose of The Study-The purpose of this study is to assess the efficacy of a planned education programme in improving eligible couples' awareness of family planning methods. Methodology- For this investigation, a pre-experimental one-group pretest-posttest design will be used. A handy sample of eligible couples dwelling in Gwalior City's specified urban region will be included. The planned teaching programme, which will include structured sessions on various family planning methods, their benefits, risks, and proper use, will be executed. A systematic questionnaire will be used to collect data before and after the instructional programme. The data will be analysed statistically using relevant methodologies. Results: This study's findings will shed light on how well the proposed teaching programme will go in educating eligible couples about family planning options. The degree of knowledge increase will be shown by comparing the pretest and posttest results. Conclusion-The study's findings will help comprehend how a planned training programme would affect how well-informed eligible couples in an urban area are about family planning options. The findings can be used to guide the creation of focused educational initiatives and regulations that support family planning and reproductive health in contexts like these.